Virological failure and risk factors among people living with HIV taking second-line ART in Addis Ababa, Ethiopia - Bekelech Bayou Feyissa; Abay Sisay; Eugene Lee Davids; Anteneh Yalew; Geoffrey Setswe (PLoS ONE, 2026)
Background Virological failure (VF) presents significant challenges in the emergence of drug resistance, and elevated risk of transmission, higher mortality rates, and a diminished quality of life. Various factors contribute to VF, but documented information on this issue is lacking in Ethiopia. Therefore, this study aimed to assess the prevalence of VF and identify the risk factors among people living with HIV who are on second-line antiretroviral treatment (ART). Methods A concurrent mixed-method study using quantitative and qualitative data was conducted at selected hospitals in Addis Ababa, Ethiopia. The analysis was conducted using SPSS version 28, Stata version 18.5, and R for quantitative data and thematic analysis with Atlas.ti version 24 software was used for qualitative data. Result Among 369 adults living with HIV taking second-line ART enrolled in the study, 191 (52%) were male with a median age of 44 years. The prevalence of VF was 55 (14.9%, 95% CI: 11, 19), with an incidence density of 27.2 per 10,000 person months (95% CI 21.1, 35.5). Lost to follow-up significantly increased VF risk [AHR: 2.52 (95% CI: 1.35, 4.69, p-value: 0.004)]. Patients transferred from other health facilities were two times at higher risk of VF compared to those receiving ART at the same facility [AHR: 1.97 (95% CI: 1.07, 3–64, p-value: 0.029)]. Likewise, clients with a history of regimen change were at a higher risk of VF [AHR = 2.05, (95% CI: 1.08, 3.88, p-value = 0.027)]. The qualitative data also supported these findings. Conclusion This study underscores the need for improved ART adherence and consistent care to reduce virological failure in PLHIV to improve the quality of life.